STRATEGI PEMBANGUNAN DESA SANGAT TERTINGGAL OLEH PEMERINTAH KABUPATEN KAMPAR TAHUN 2021-2022 - Putri, Ninda Amelia; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research discusses the development strategy of very disadvantaged villages and sees how the efforts of the Regional Government and related Regional Apparatus Organizations in alleviating the problem of very disadvantaged villages in Kampar Regency. Because based on the Village Development Index data which consists of three composite indices, namely the Social Resilience Index, Economic Resilience Index and Environmental Resilience Index in 2021-2022, it was found that 24 very underdeveloped villages were in Riau Province and as many as 23 very underdeveloped villages were in Kampar Regency, precisely in the Kampar Kiri Hulu District. Therefore, this research aims to find out the development strategies used by the local government in accelerating development in very underdeveloped village areas, especially since 9 very underdeveloped villages are located in the Bukit Rimbang Bukit Baling Wildlife Sanctuary conservation area. The research methodology used by the author is descriptive qualitative. The type of data used is primary obtained through interviews and secondary data data comes from documents related to the research. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions. The author uses Rahardjo Adisasmita's theory of development strategies consisting of 4 strategies, namely the growth strategy or growth strategy, the walfare strategy or welfare strategy, the responsive strategy or strategy that is responsive to community needs and the holistic strategy or integrated strategy. The results showed that the most dominant welfare strategy or the walfare strategy was carried out by the Kampar Regency Government where the government was busy improving the welfare of the community through development programs, especially in the field of road and bridge infrastructure facilities and infrastructure. Then for a strategy that is responsive to community needs or the holistic strategy, the Kampar Regency Government has not been able to meet community demand for internet needs in 20 villages in Kampar Kiri Hulu District. BBKSDA Riau Province also takes an important position in community empowerment in the suakamargasatwa area. Keywords: Strategy, Development, Highly Disadvantaged Villages